Synthesis of Water-soluble single-walled nanotubes by Functionalization Via Esterification (Global Journal of Science Frontier Research, 2012)
Water soluble compoundes were attached to single-walled carbon nanotubes (SWNTs) to form watersoluble nano dyes. functionalized SWNTs were then characterized by Fourier Transform Infrared spectroscopy (FT-IR), Raman spectroscopy, scanning electron microscopy (SEM) and UV analysis. The product can be dissolved in water and High-resolution transmission electron microscope images showed that the SWNTs were efficiently functionalized, thus the p-stacking interaction between aromatic rings and COOH of SWNTs was considered responsible for the high solubility and High transmission electron in singlewall nanotubes.
Keywords: Functionalized CNTs; Singlewalled carbon nanotubes; Water soluble compoundes